Dietary Analysis of Cold Arid Inhabitants of Leh (Ladakh): Need for Integrated Agricultural Systems - Srivastva, Soma; Kumar, Suresh; Roy, Murari Mohan; Angmo, Rimzin (Annals of Arid Zone, 2016)
The study uses cross-sectional data of a sample of 178 individuals from eight villages in Leh district of Jammu & Kashmir state in India. Dietary diversity and availability of nutrients are assessed in the overall socio-demographic, agricultural and nutritional systems. Subjective and objective measures like socio-demographic survey, household dietary diversity score and 24 hr dietary recall were used. It emerged that the region has adequate level of diversity in the diet, however, further improvement is needed to have balanced nutrition. The role of Public Distribution System (PDS) is very crucial in achieving the same. There is a need for designed agricultural system with integration of field crops, horticulture and livestock. Crop diversification with inclusion of high value agricultural crops and introduction of new tuber and cereal varieties like finger millet (Eleusine coracana) and maize (Zea mays) was suggested to imply the self-reliance in food production and gradually decrease the dependency on subsidized food grains. Legumes and dairy products were significantly deficient in their diet thus interventions are required also to revive the traditional livestock based livelihoods for better nutrition and remuneration. Key words: Dietary analysis, cold desert, Leh (Ladakh).